The requirements of agricultural investment in Iraq in light of his accession Of the World Trade Organization - علي, صباح نعمة; عبد الحسين, دعاء علي (Journal of Economics and Administrative Sciences, 2024)
Abstract                         Agricultural investment is one of the main requirements in most economies of the world for its importance in the development of the agricultural sector through the agricultural and technological infrastructure and agricultural research, as well as its impact on most economic, social and service activities, especially if managed and employed scientifically, which generates income and productive capacities and services and new commodities, Unemployed as agricultural investments in Iraq fell significantly after 2003 due to economic, political, social and security factors, which led to the deterioration of production and low contribution to GDP, which led to rely on global markets to provide agricultural commodities to meet domestic demand, so Iraq hopes to reach the level that qualify for the accession process has focused on the problem of the study that accession to the World Trade Organization is a major challenge to developing countries, especially that Iraq is among these countries is facing problems Or challenges facing the agricultural investment process in Iraq, including infrastructure, agricultural development challenges, poor performance of policies and trade, creating an environment not attractive to investment reflected on the weakness of agricultural investments in Iraq. The importance of the study is highlighted by the importance of agricultural investment in the development of the agricultural sector and the development of agricultural research and technology to achieve food security and the recognition of Iraq's obligations towards the organization as an observer member and the impact of the implementation of the Agreement on Agriculture on the agricultural sector in Iraq and to address the experiences of selected countries to identify the process of accession and benefit from The study aimed to study and analyze the reality of agricultural investment and the challenges facing it that created an environment that repels the investment process and the proposed strategy for activating agricultural investment. And the importance of agricultural investment in economic and agricultural activity and develop the reality of Iraqi agriculture and attract capital to the agricultural sector, as well as the statement of expected effects on agricultural investment in Iraq in the case of accession to the World Trade Organization and the obligations imposed on the direction of the organization to obtain the And the impact of the Agreement on Agriculture under the World Trade Organization on Iraq.